TINDAKAN HUKUM KEIMIGRASIAN DALAM PENYALAHGUNAAN VISA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN DI KOTA SAMARINDA - MELISA KARTIKA SARI (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTLaw enforcement against foreign nationals (foreigners) who violate visa / permit in Samarinda accordance with Act No. 6 of 2011 on Immigration, by way of supervisory administrative formality foreign nationals (foreigners) who will enter Indonesia, especially Samarinda, and provide administrative actions to which one of them violates a residence permit that is paying the cost burden. Terms obtain residence permits which foreigners have a passport and a valid visa and is not included in the list of deterrence. The factors that influence in law enforcement at the Immigration Office Samarinda firstly supporting factors, Immigration Office Samarinda cooperate with related agencies such as the Police of the Republic of Indonesia, Police Samarinda and its staff, the Office of Manpower and Transmigration Samarinda and public participation as well as active guarantor to give an justified the presence and activities of foreign nationals (foreigners), both inhibiting factor that is long distance to reach all areas of Samarinda Immigration Office, and the number of law enforcement teams at the Immigration Office Samarinda inadequate. Therefore the Immigration Office Samarinda need to increase human resources (HR) to establish and train civil servant investigators (investigators) in the framework of prosecution of foreigners. Samarinda Immigration Office should coordinate with relevant agencies in order to control foreign nationals (foreigners) and the actions of intelligence operations.Keywords: Abuse visas, immigration.